A Framework for Discipline-Specific Learning, Teaching, and Assessment of Psychomotor Skills in Higher Education - Matshete Chweu, Eric (CV Kalimasada Group, 2025)
This study investigated the extent to which psychomotor skills are assessed in higher education and proposed a framework to enhance the assessment of these skills. While higher education institutions globally assess students' knowledge thoroughly, the assessment of psychomotor skills is often implicit, unsystematic, and inadequate. This research aims to address this gap by using Bloom's taxonomy to develop a comprehensive assessment framework. The research question was: